Sendingwetenskap vir die derde millennium - Deel II - Meiring, P. G. J. (Verbum et ecclesia, 1999)
Missiology for the third millennium - Part II This article contains the second part of professor P. G. J. Meiring’s inaugural lecture, on accepting the position of Head of the Department of Science of Mission and Science of Religion (Godsdiens- en Sendingwetenskap) at the Theological Faculty, University of Pretoria.